In Between ... - Wong, Tristan; Greenaway, Jefa; Milliken, Jordyn; Puls, Aaron; Grant, Elizabeth; Parsons, Ash (RMIT University, 2024)
BACKGROUND: The exhibition In Between for the Australian pavilion studies architecture's capacity to strengthen cultural connections and understanding between non-Indigenous and First Nations peoples. In Between presents a collection of architectural projects and processes selected for their powerful representation of Indigenous and First Nations peoples and cultures; projects that enable cross cultural exchange and highlight the value of Indigenous knowledges for improving the built environment. The research explores different approaches, across a variety of architectural typologies and scales, working to shared agendas and a consistency of thinking demonstrating a level of cultural maturity within the built environment disciplines where cultural collaboration and exchange are possible. CONTRIBUTION: Due to the pandemic, In Between was devised as physical immersive exhibit and an online portal (which required new technologies). It encourages discourses of the shared challenges faced across Oceania ...